2005
DOI: 10.1210/en.2004-1379
|View full text |Cite
|
Sign up to set email alerts
|

The Endogenous Growth Hormone Secretagogue (Ghrelin) Is Synthesized and Secreted by Chondrocytes

Abstract: Ghrelin, the endogenous ligand for the GH secretagogue receptor (GHS-R), is a recently isolated hormone, prevalently expressed in stomach but also in other tissues such as hypothalamus and placenta. This novel acylated peptide acts at a central level to stimulate GH secretion and, notably, to regulate food intake. However, the existence of further, as yet unknown, effects or presence of ghrelin in peripheral tissues cannot be ruled out. In this report, we provide clear evidence for the expression of ghrelin pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(59 citation statements)
references
References 34 publications
3
52
0
4
Order By: Relevance
“…Likewise, GOAT was also expressed in human immortalized chondrocyte cell lines and in human cultured primary chondrocytes, demonstrating that chondrocytes were equipped with biochemical machinery for the synthesis of acylated ghrelin ). Moreover, ghrelin was synthesized and secreted by chondrocytes (Caminos et al, 2005). These data suggest a novel role of the ghrelin axis in prehypertrophic and hypertrophic chondrocyte differentiation during endochondral ossification.…”
Section: G Bone Metabolismmentioning
confidence: 70%
“…Likewise, GOAT was also expressed in human immortalized chondrocyte cell lines and in human cultured primary chondrocytes, demonstrating that chondrocytes were equipped with biochemical machinery for the synthesis of acylated ghrelin ). Moreover, ghrelin was synthesized and secreted by chondrocytes (Caminos et al, 2005). These data suggest a novel role of the ghrelin axis in prehypertrophic and hypertrophic chondrocyte differentiation during endochondral ossification.…”
Section: G Bone Metabolismmentioning
confidence: 70%
“…It is possible that other nutrition-related hormones released from the gut before or during feeding, such as ghrelin and gastric inhibitory polypeptide (GIP), may be involved in the CNP reduction we observed during caloric restriction. Ghrelin, which is increased in sheep by the anticipation of food (36), inhibits chondrocyte metabolic activity in vitro (6) and is likely to be increased in the caloric-restricted lambs. Also, plasma concentrations of GIP in lambs are known to increase after milk intake (23) and therefore are likely to be low during caloric restriction.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the multiplicity of ghrelin actions affecting GH secretion, food intake, glucose homeostasis, cardiovascular, gastrointestinal and immune functions, it has been reported that ghrelin also plays an important role in bone formation (62) and regulation of chondrocyte metabolism in cartilage (63). Therefore, the expression of GOAT mRNA was also assessed in murine and human chondrocytes.…”
Section: Goat Mrna Expression and Its Regulationmentioning
confidence: 99%